Ugotavljanje in izkoriščanje skritih logističnih zmožnosti podjetja - Kušar, Janez (Strojniški vestnik, 2005)
Companies are nowadays confronted with new challenges: simultaneously they aredealing with the globalization of business and acting on local markets, thestandardization and customization of products for fastidious customers and increased competition. In these circumstances the only successful companies are those which can respond quickly to market changes, i.e., they have a shortresponse time for the fulfilment of customer requirements (a short delivery time and reliable delivery in addition to a competitive price and high quality). Consequently, a reduction of the mean inventory, the range and the lead time of the working systems in the company is an ever increasing strategy that ensures the customer's satisfaction and an increase in growth and profit for the company. The article shows how the tools for modelling the flow of orders through working systems can be used to find and exploit the hidden logistic potentials of working systems in a company. Here we present the results of finding and exploiting the hidden logistic potentials of working systems in the tool-production department of the "ETI Ltd." company from Izlake, Slovenia.
Keywords: sistemi delovni; časi pretočni; stanja; učinki; zmožnosti logistične; logistika; delovni sistemi; pretočni čas; podjetja